Določitev trajno varovanih kmetijskih zemljišč – metodološki poskus ( = Determination of prime agricultural land conservation areas – a methodological attempt) - Nadja Penko Seidl; Mojca Golobič (Geodetski Vestnik, 2015)
This paper examines the problem of agricultural land decreasing in Slovenia. It discusses different approaches to agricultural land conservation and presents some proposals for the establishment of areas of prime agricultural land. While the current system of agricultural land conservation is obviously inefficient, a new concept for agricultural land conservation is being prepared. This was also the challenge for the students of the first year of a master’s degree programme in landscape architecture; they have developed some proposals for prime agricultural land conservation. The most important emphases to be mentioned are: to consider regional and local characteristics of agricultural production, to assure maximum possible self-sufficiency, to introduce new technologies, and to preserve cultural landscape.